An AN ANALYSIS OF ELEVENTH-GRADE STUDENTS' SPEAKING ANXIETY TOWARDS SPEAKING PERFORMANCE AT MA AL-SHIGHOR: Identifying Factors Contributing to Speaking Anxiety and Its Impact on Students' Oral Proficiency in English Language Learning. - Hasanah, Uswatun (NextGen Education Review Journal, 2024)
This study analyzes the level of speaking anxiety of grade XI students at MA AlShighor and its impact on speaking performance in formal and informal situations. The method used is descriptive qualitative with closed and open questionnaires, in-depth interviews, and participant observation. The results show that speaking anxiety affects students' fluency, clarity, intonation, and self-confidence. Students with high anxiety have difficulty organizing thoughts logically, resulting in decreased quality of presentation and verbal interaction. Factors such as fear of mistakes, concerns about negative assessment, and previous negative experiences also increase anxiety. Effective teaching strategies are recommended, including relaxation techniques such as breathing exercises and interaction-based learning through small group speaking practice and simulation. This approach is expected to significantly improve students' selfconfidence and speaking ability.